Spaniwood? English Language Spanish Films since the 1990s - Cristina Sánchez-Conejero (Studies in 20th & 21st Century Literature, 2009)
Is there such a thing as “Spanish identity”? If so, what are the characteristics that best define it? Since the early 1990s we have observed a movement toward young Spanish directors interested in making a different kind of cinema that departs markedly from the lighthearted landismo of the 70s and, later, the indulgent almodovarismo of the 80s. These new directors—as well as producers and actors—are interested in reaching out to wider audiences, in and outside of Spain. The internationalization they pursue comes, in many cases, with an adoption of the English language in their works. This multicultural cinema presents a dilemma: what characteristics define a “Spanish” movie? This study explores and argues for the use of the terms “world cinema” and “glocal cinema” in favor of outdated notions of “national cinema” while pointing out the need for defining clear notions of the new, plural and inclusive forms of Spanishness evident in films today.
Keywords: English language; Spanish films; Spanish identity; landismo; almodovarismo; internationalization; cinema; world cinema; glocal cinema; national cinema